The effect of calcination temperature on ZnO crystals based on emission spectrum from photoluminescence characterization - Aprilia, Annisa; Askariyya, Javida; Riveli, Nowo; Safriani, Lusi; Fitrilawati, Fitrilawati (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2025)
This study synthesized ZnO powder using the sol-gel method to investigate its optical properties. ZnO samples were calcined at 150°C, 300°C, and 450°C under nitrogen (N₂) flow. TGA/DTA analysis showed that most solvent residues or impurities were decomposed at 450°C. This result is supported by the XRD results, which showed an increase in the degree of crystallinity with increasing temperature. At the same time, the hexagonal wurtzite structure of ZnO gel remained intact after calcination. SEM-EDS analysis revealed agglomerated morphology and a disproportionate Zn:O ratio in all samples, with excess Zn atoms. This is probably attributed to the presence of interstitial Zn defects. The photoluminescence spectrum showed higher intensity in the UV region compared to the visible range, indicating good crystallinity. The blue shift in the emission with increasing temperature stated the presence of several different defects in the material. In particular, the green emission associated with oxygen vacancies is absent for the sample calcinated at 450°C. This result confirms that higher calcination temperature reduces defects and increases crystallinity